Perception Analysis of the 24-Hour Operation Ban on Madura Stalls - Vita Febria Mutia Zein; Muhammad Aras Prabowo; Habsyah Fitri Aryani (Trescode Green Organization, 2025)
Analyzing the potential impact of the 24-hour operational ban on stalls madura on the socioeconomic dynamics of the community, especially in the Matraman area in central Jakarta, is the main objective of this research. Researchers envision Jakarta as a benchmark, if the 24-hour operational ban policy for Madura stalls is implemented nationally. So that this research can provide an overview of the impact that will occur if the policy is implemented. Through data collection, both in the form of previous research on related themes and data from interviews with madura shop owners at the research location, it becomes a source of reference in compiling this research. The results of adjustments to the data and facts show that there is a suspicion of a conflict of interest by the government in initiating the policy. Therefore, due to the economic and social impacts caused by injustice, a more massive government role is needed.